Representation of Nationalism in the Practice of Freedom of High School Students in Kediri - Naja, Anang Darun; Zainiyati, Husniyatus Salamah; Asrohah, Hanun (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze and describe the representation of freedom as a manifestation of the spirit of nationalism in high school students in Kediri Regency. The approach used is qualitative with a descriptive research type. The research subjects involved students, homeroom teachers, and school principals. Data collection techniques were conducted through interviews, observation, and documentation. Data analysis used the Miles & Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing. The results showed that most students understood the concept of freedom from the laws and regulations, while others still had a wrong understanding. The phenomena experienced by students, including the abuse of freedom by unscrupulous officials, affect their perspective on the value of freedom and nationalism. Therefore, government officials must act with discipline as a form of character education for the younger generation. This study contributes to strengthening the nationalist spirit of the millennial generation by using Kartodirdjo's theory as a foundation for understanding the dynamics of the national spirit amidst the challenges of the times.